Syria in Regional Security System in 2000-2011 - M. S. Khodynskaya-Golenichsheva; M. A. Sapronova (Научный диалог)
Syria’s role in regional security in the period of 2000-2011 is discussed. Special attention is paid to the coming to power of Bashar Assad, marked by attempts to soften the confrontation of Syria with regional and extra-regional powers, while simultaneously building a flexible system of situational alliances. The relevance of the study is determined by the fact that an independent foreign policy of Syria have angered the US, which during the presidency of George W. Bush sought to establish a doctrine of American leadership in several regions of the world. It is proved that the aggravation of contradictions with the USA and Israel objectively was promoted by the Second Intifada, since Damascus has traditionally supported the Palestinian people’s struggle for national self-determination. Special attention is paid to the fact that Syria made a “turn to the East,” was to improve relations with Iran and Russia. The novelty of the research is seen in the fact that the reasons are shown for the uncompromising attitude of the West towards the fate of the Syrian political regime in the civil war in the country, namely that the government of Bashar Assad has intensified confrontation with the West.